Working Capital Management and Corporate Profitability: Evidence from Panel data analysis of selected quoted companies in Sri Lanka - Anandasayanan, S. (University of Sairam, 2011)
The working capital management plays an important role for the success or failure of firm in business because of its effect on firm’s profitability as well on liquidity. An optimal working capital management is expected to contribute positively to the creation of firm value. To reach optimal working capital management firm’s manager should control the tradeoff between profitability and liquidity accurately. The study aimed to provide empirical evidence about the effects of working capital management on profitability for a panel made up of a sample of eighty Sri Lankan listed firms for the period 2003 to 2009.The study utilized panel data econometrics in a pooled regression, where time series and cross sectional observations were combined and estimated.. The study is based on secondary data collected from 80 listed firms in Sri Lanka stock market. The study found a significant negative relationship between net operating profitability and the average collection period, inventory turnover in days and average cash conversion cycle. These results suggest that managers can create value for their shareholders if the firms manage their working capital in more efficient ways by reducing the number of days accounts receivable and inventories to a reasonable minimum.
Keywords: Net operating profitability; The average collection period; Inventory turnover in days; Average cash conversion cycle